Proces budżetowania w Zespole Elektrowni Dolna Odra SA - Sawicka-Kluźniak, Zofia (Budgeting process in power plant company Dolna Odra SA, 2008)
The objective of the article is to present the prerequisites and assumptions of the budgeting system in power plant Dolna Odra SA. Budgeting provides the company with cost optimization, plan control and improves the organization of management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 413-418